Gray, Wendell. Outhouse on the Gray stage in Quidi Vidi. - Sawden, Kari (2013)
Outhouse built by Joseph "Skipper" Gray, father to Wendell and Balfour Gray. It survived the destruction of the stage in the winter of 2009.